Retinopathy in type 2 diabetic patients with microalbuminuria - Reddy, SC; Khin, YM; Nurjahan, MI; Ramli, A (Nepalese Journal of Ophthalmology, 2013)
Objective: To determine the prevalence of retinopathy in type 2 diabetic patients with micoalbuminuria and to evaluate the association of risk factors with prevalence of retinopathy in these patients. Material and methods: A fundus examination of 137 patients suffering from type 2 diabetes mellitus with microalbuminuria was done, with direct ophthalmoscope/ binocular indirect ophthalmoscope after dilating the pupils with 1 % tropicamide eye drops. Retinal changes were graded as no retinopathy, non-proliferative retinopathy, proliferative retinopathy and maculopathy. The association of the duration of diabetes, control of diabetes, hypertension, hyperlipidemia, smoking, obesity and peripheral neuropathy was assessed with the prevalence of retinopathy in these patents. Results: The mean age of the patients was 58 years (range 35 - 79 years); 62 % were females, and 49.6 % were Chinese. Diabetic retinopathy was seen in 36.5 % of the patients — non proliferative in 29.2 %, proliferative in 7.3 % and maculopathy in 5.1 % of patients. A longer duration of diabetes (p = 0.002), poor control of diabetes (p = 0.002), presence of hypertension (p = 0.03), and presence of peripheral neuropathy (p = 0.001) were significantly associated with the prevalence of retinopathy; while hyperlipidemia (p = 0.29), smoking (p = 0.43) and obesity (p = 0.43) were not associated with retinopathy. Conclusion: Retinopathy was seen in 36.5 % of type 2 diabetic patients with microalbuminuria; 7.3 % had proliferative retinopathy and 5.1 % maculopathy (both sight threatening changes). All diabetic patients with microalbuminuria should be screened for retinopathy so that treatment can be instituted in the required patients to prevent ocular morbidity/ blindness. Nepal J Ophthalmol 2013; 5(9):69-74 DOI: http://dx.doi.org/10.3126/nepjoph.v5i1.7830